2001
DOI: 10.1073/pnas.051584498
|View full text |Cite
|
Sign up to set email alerts
|

Indirect recognition of allopeptides promotes the development of cardiac allograft vasculopathy

Abstract: Graft loss from chronic rejection has become the major obstacle to the long-term success of whole organ transplantation. In cardiac allografts, chronic rejection is manifested as a diffuse and accelerated form of arteriosclerosis, termed cardiac allograft vasculopathy. It has been suggested that T-cell recognition of processed alloantigens (allopeptides) presented by recipient antigen-presenting cells through the indirect pathway of allorecognition plays a critical role in the development and progression of ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
94
0
5

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(106 citation statements)
references
References 35 publications
(37 reference statements)
7
94
0
5
Order By: Relevance
“…These immunosuppressive agents, however, are inadequate for averting late graft loss caused by chronic rejection. There is increasing evidence that indirect allo-recognition plays a critical role in chronic rejection [6,23,421. However, the types of alloreactive responses generated by this pathway that precipitate chronic rejection are not well characterized.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These immunosuppressive agents, however, are inadequate for averting late graft loss caused by chronic rejection. There is increasing evidence that indirect allo-recognition plays a critical role in chronic rejection [6,23,421. However, the types of alloreactive responses generated by this pathway that precipitate chronic rejection are not well characterized.…”
Section: Discussionmentioning
confidence: 99%
“…Similar data were reported by Vella et al [42] in kidney allograft recipients experiencing chronic rejection. Direct experimental data for the role of indirect recognition in chronic allograft rejection were recently provided by Lee et al [23], who demonstrated that pre-immunization of pigs with donor class-I allopeptides promoted the development of chronic cardiac allograft rejection.…”
Section: Introductionmentioning
confidence: 99%
“…The contribution of the indirect pathway to allorecognition and to both acute (6) and chronic (7,8) forms of allograft rejection has also been validated by numerous studies. One pertinent example is that of Auchincloss et al (9), who reported the rapid rejection of skin allografts derived from MHC class II-knockout mice, thereby demonstrating that indirect recognition alone can be an effective pathway of alloreactivity in this small animal model.…”
mentioning
confidence: 97%
“…19,20,31,[35][36][37] The complexity of such transplant-reactive immune repertoires has limited our ability to independently test whether antigen location in the target organ affects the downstream pathological consequences. In an effort to circumvent this limitation, we performed a series of experiments using a CD4 T cell receptor (TCR) transgenic mouse as transplant recipients such that we could control the specificity of the induced effector T cells.…”
mentioning
confidence: 99%